DAMPAK KAMPUS UNIVERSITAS NEGERI SEMARANG TERHADAP PERUBAHAN SOSIAL EKONOMI MASYARAKAT KELURAHAN SEKARAN KECAMATAN GUNUNGPATI KOTA SEMARANG - Wanty Eka Jayanti (Jurnal Khatulistiwa Informatika, 2014)
The focus of this research is the Socio-Economic Changes that occurred in village communities have now caused by the campus that began Unnes active since 1990. The problem raised is how social change is a change in social structure and lifestyle and economic change in the form of livelihood and economic changes experienced by the family of village communities have now due to the presence Unnes campus. Goals to be achieved is to know how to shape socio-economic changes experienced since the existence of the Unnes campus community in the village have now. The method used in this research is qualitative research is research that produces descriptive data analysis. While data collection techniques used were interviews, observation, and documentation. in analyzing the data, after collecting data, researchers used a qualitative research phase with an interactive model. The results showed that the socio-economic changes experienced by village communities have now quite significant. Changes that occur in the structure of society which has developed the organizational awareness, people's lifestyle is changing and has followed the trend of today, the livelihood of the majority of farmers had previously been changed into a majority of both employers and trade services. Changes in livelihoods is what ultimately led to increased family income. Poor families reduced level, and most people have can meet and / or provide for his own household. these changes is the impact of causing the existence Unnes campus developments and the gradual development of infrastructure. So that access to information on community absorption quickly also availability of facilities to the city of Semarang, which is very adequate. The conclusion is that development in the Village Unnes have now, by accident has many positive contributions that cause the changes towards the better for the life of the local community. The presence of students with all their needs as a very good business area for the community, although there are some people who can not take advantage of these opportunities because of limited capital and experience in entrepreneurship.Keywords: Unnes Campus Impact, Social Change, Community Economic Change.